Utilization of Climate-Smart Agricultural Practices Among Rural Farmers in Cross River State, Nigeria - Friday Ogar Idiku; Emmanuel Ekpo Archibong; Ekpenyong Nsa Essien; Victoria Francis Ediene; Emmanuel Ohara Eremi; Comfort Felix Aya (Universitas Panji Sakti, 2026)
Climate change poses a significant threat to agricultural productivity and food security in Nigeria. This study assessed the utilization of Climate Smart Agricultural (CSA) practices by describing the socio-economic characteristics of rural farmers, identifying their sources of information on CSA, documenting CSA practices currently adopted, and examining the constraints hindering widespread utilization. The key findings are that the majority of respondents were male (59.6%) and youths aged 20–35 years (59.6%), with most being married (59.6%) and having small households (79.8%). Although many earned a modest income (₦150,000–₦250,000 annually). A majority lacked access to credit (82.6%), which is a major limitation to CSA investment. CSA information access shows that Radio/TV (60.6%) was the main information source, and only 21.1% received CSA information from extension agents. CSA adoption and duration indicated that conservation agriculture was the most adopted practice (68.8%), and the majority (62.3%) had adopted CSA practices within the last two years, indicating relatively recent exposure while motivations for CSA adoption were improved yield (58.7%), followed by reduced cost (27.5%) and improved soil fertility (13.8%). The challenges to CSA adoption were a lack of technical knowledge (55.1%) and limited access to credit (27.5%) as dominant constraints. However, education (p=0.045, r=0.654) and sex (p=0.036, r=0.560) were significantly related to adoption of CSA practices. Similarly, social media (p=0.007, r=0.429) had a strong, positive relationship with utilization of CSA practices, while Radio/TV (p=0.062, r=0.401), though not too significant, but the positive value, indicates their importance. Therefore, CSA practices and interventions should be holistic to transform agricultural development.